Experimental Investigation on Zonal Structure in Drag-Reducing Channel Flow with Surfactant Additives - Masaaki Motozawa (Advances in Mechanical Engineering, 2011)
The spatial structure of a drag-reducing channel flow with surfactant additives in a two-dimensional channel was investigated experimentally. We carried out detailed measurements of the instantaneous velocity in the streamwise wall-normal plane and streamwise spanwise plane by using particle image velocimetry (PIV). The surfactant used in this experiment is a kind of cationic surfactant CTAC. The weight concentrations of the CTAC solution were 25 and 40 ppm on the flow. We considered the effects of Reynolds number ranging from 10000 to 25000 and the weight concentration of CTAC. The results of this paper showed that in the drag-reducing flow, there appeared an area where the root mean square of streamwise velocity fluctuation and the vorticity fluctuation sharply decreased. This indicated that two layers with different turbulent structure coexisted on the boundary of this area. Moreover, these layers had characteristic flow structures, as confirmed by observation of the instantaneous vorticity fluctuation map.